ESENSI PENGALAMAN KESETARAAN GENDER PEKERJA PEREMPUAN DI PT. PLN (PERSERO) UNIT INDUK DISTRIBUSI JAWA TENGAH DAN D.I.YOGYAKARTA - Marisa Arum Larasati; Sunarto Sunarto; Lintang Ratri Rahmiaji (Interaksi Online, 2022)
Gender inequality in Indonesia is still common, in this case, there are still some problems regarding gender equality in career development in companies, especially for female employees. The company most likely considers that women do not have the ability like men. One of the State-Owned Enterprises (BUMN), namely PT. PLN (Persero) Central Java and D.I.Yogyakarta Main Distribution Units have implemented rules regarding gender equality that do not differentiate between male employees and female employees in occupying positions. This study aims to understand the essence of the experience of gender equality in the career development of female employees. This is qualitative research that uses a critical paradigm with a critical phenomenology approach. The theory used in this research is Critical Organizational Communication Theory and Standpoint Theory. The data collection method used in this study was to conduct in-depth interviews by informants of 5 female employees who had a tenure of fewer than 5 years, more than 5-20 years, and over 20 years. The results show that this company has been dominated by male employees, it can be seen from employees to company leaders. When recruiting employees at PT. PLN (Persero) Main Unit Distribution Central Java and Yogyakarta, the difference in the number of male employees is 400 people and there are 18 female employees in the field. Experience of female workers at PT. PLN (Persero) Central Java and D.I.Yogyakarta Distribution Parent Units in developing employee careers to become structural officers have been determined through an application that has been provided to see the criteria of prospective candidates and follow the fit and proper test that has been held by the HR field. The company provides opportunities for female employees to develop their careers at PT. PLN (Persero) Main Unit Distribution Central Java and Yogyakarta, but each individual has obstacles to developing his career with special considerations such as family and work area placement. Thus, positions that have occupied structural positions tend to be dominated by male employees who do not take much consideration. However, female employees can still be involved in decision-making at work meetings and when employees are active at PT. PLN (Persero) Main Unit Distribution Central Java and Yogyakarta are determined based on the education level of male and female employees, not based on the gender of the employee.